HAMBATAN PENERJEMAHAN TEKS BAHASA ARAB KE DALAM BAHASA INDONESIA: PENGALAMAN MAHASISWA SASTRA ARAB UNIVERSITAS NEGERI MALANG - Irhamni Irhamni (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This paper is intended to describe the result of a research focusing on the students’  translation  problems  in  translating  Arabic  texts  into  Indonesian.  The problems result from the students’ understanding  and retelling (re-expressing)  the results  of  the  understanding  during  the  translation  process.  In  this  study,  the researcher is applying descriptive-qualitative method. The result shows that the students’ problems in translating have close relation with (1) the students’ understanding  of  linguistics  structure  and  non-linguistics  structure,  and  (2)  the students’ problems in retelling (re-expressing) the results of their reading regarding linguistics and non linguistics problem.